Performance Evaluation of Polling-Based OPC UA Client-Server Communication in Industrial PLC Systems : An Experimental Load Study on OPC UA Performance Using Siemens S7-1500 PLC - Vuorinen, Reko (My University, 2026)
As the adoption of Industrial Internet of Things (IIoT) technologies is becoming more common, it has increased the use of standardized communication protocols for integrating industrial devices and information system in a production environment. Open Platform Communications Unified Architecture (OPC UA) is widely used technology for making interoperable communication possible in industrial plants. However, when OPC UA experiences increased communication load, the OPC UA client-server solutions may show performance limitations which makes the system less reliable. This thesis investigates the performance behaviour of polling-based OPC UA client-server communication in a pharmaceutical production environment. Thesis utilizes programmable logic controller (PLC) as the OPC UA client. The study is conducted in collaboration with a pharmaceutical manufacturing company. In their production, communication anomalies had been observed under increased load conditions. To research this a quantitative research method was used in order to evaluate the effects of OPC UA on given communication performance. This was done by varying the number of nodes per read request, payload size, polling interval, and parallel read jobs in given communication setup. The results of the study show that the number of nodes per request has the greatest influence on client-side processing delay. In the used testbed setup, this leads to increased polling drift under high communication loads. The amount of total communication data which is determined by payload size and number of nodes together, was found to have the most affect for round-trip (RTT) time and jitter measured in given setup. Parallel read jobs had only a small direct impact on performance within the given hardware limits. Observed anomalies coming from duplicates and missed values, were believed to be primarily caused by timing mismatches between client polling cycles and server update cycles. Overall, this study gives insight of the performance characteristics of polling-based OPC UA communication. It introduces a testbed that enables systematic analysing of the communication and optimization of polling configuration timings. OPC UA subscription model is also shown as a potentially more robust event-based alternative for the studied industrial use case.

Teollisen internetin (Industrial Internet of Things, IIoT) teknologioiden yleistyminen on lisännyt standardoitujen tiedonsiirtoprotokollien käyttöä teollisissa laitteissa ja järjestelmissä. Open Platform Communications Unified Architecture (OPC UA) on yksi yleisimmin käytetyistä teknologioista yhtenäistetyn tiedonsiirron mahdollistamiseksi teollisissa ympäristöissä. Suurilla tiedonsiirtomäärillä, OPC UA asiakas-palvelin kommunikaatiossa on havaittu esiintyvän rajoitteita ja vikakäyttäytymistä, jotka vaikuttavat järjestelmän luotettavuuteen. Tässä työssä tutkitaan OPC-asiakkaan lukupyyntöihin pohjautuvaan OPC UA asiakas-palvelin kommunikaation suorituskykyä teollisessa ympäristössä hyödyntäen ohjelmoitavaa logiikkaa (PLC) OPC UA asiakkaana. Tutkimus toteutettiin yhteistyössä lääketeollisuudessa toimivan tuotantoyrityksen kanssa, jonka tiedonsiirrossa oli havaittu poikkeamia suuren tiedonsiirtomäärien yhteydessä. Tutkimuksessa hyödynnettiin kvantitatiivista kokeellista tutkimusasetelmaa, jossa kommunikaation suorituskykyä arvioitiin muuttamalla järjestelmällisesti seuraavia parametreja: lukupyynnön elementtien määrää, viestin kokoa (payload), lukupyyntöjen pyyntötiheyttä sekä rinnakkaisten lukupyyntöjen määrää. Tulokset osoittavat, että lukupyynnön elementtien määrä vaikuttaa merkittävimmin OPC-asiakkaan käsittelyviiveeseen, mikä johtaa lukyöyyntöjen viivästymiseen suurilla tiedonsiirtokuormilla testatussa järjestelmässä. Kokonaiskommunikaatiokuorman havaittiin vaikuttavan merkittävästi tiedonsiirron edestakaiseen vasteaikaan (round-trip time, RTT) ja sen vaihteluun (jitter). Tämä kokonaiskuorma määräytyy viestin koon ja elementtien yhteenlasketun kuorman perusteella. Rinnakkaisilla lukupyynnöillä oli laitevalmistajan asettamien rajoitusten puitteissa vain vähäinen vaikutus kommunikaation viiveeseen ja suorituskykyyn. Lisäksi havaitut poikkeamat, kuten duplikaatit ja puuttuvat arvot, todettiin johtuivat pääasiassa ajallisista epäsynkronoinneista OPC-asiakkaan lukupyyntösyklien ja OPC-palvelimen päivityssyklien välillä. Tutkimus tuottaa empiiristä tietoa teollisessa käytössä olevan OPC UA -kommunikaation suorituskykyominaisuuksista ja esittelee testausympäristön, joka mahdollistaa kommunikaation systemaattisen analysoinnin sekä mahdollistaa lukupyyntöjen optimoinnin. Tulokset korostavat myös OPC UA subscription mallin potentiaalia luotettavampana vaihtoehtona teolliseen kommunikaatioon tarkastellussa käyttötapauksessa.
Keywords: OPC UA; IIoT; performance evaluation; client-server communication; industrial communication; polling-based communication; teollinen internet; suorituskyvyn mittaus; asiakas-palvelin-kommunikaatio; teollinen tiedonsiirto; kyselypohjainen kommunikaatio